Defining Iran : politics of resistance - Holliday, Shabnam J. (Farnham, Surrey ; Burlington, VT : Ashgate Pub., 2011)
This book examines what it means to be Iranian and how Iranian national identity is constructed; how Islam, Iran's pre-Islamic culture, and relations with the West are dealt with and determining what is authentic and legitimate.
Discourse of national identity -- Īrānīyat and Iranian identity -- Islāmīyat and Iranian identity -- Ayatollah Khamene'i's Islamist discourse of national identity -- Islamist-Iranian discourse of national identity : Khatami's state counter-discourse -- A contemporary Iranian identity : towards a discourse of Iranian civic national identity?
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Iran -- Politics and government; Nationalism -- Iran; Political culture -- Iran; Iran -- History; Iran; Iran; Electronic books